3D QSAR based design of novel oxindole derivative as 5HT7 inhibitors. (June 2014) - Chitta, Aparna; Sivan, Sree Kanth; Manga, Vijjulatha
Abstract To understand the structural requirements of 5-hydroxytryptamine (5HT7) receptor inhibitors and to design new ligands against 5HT7 receptor with enhanced inhibitory potency, a three-dimensional quantitative structure–activity relationship study with comparative molecular field analysis (CoMFA) and comparative molecular similarity indices analysis (CoMSIA) for a data set of 56 molecules consisting of oxindole, tetrahydronaphthalene, aryl ketone substituted arylpiperazinealkylamide derivatives was performed. Derived model showed good statistical reliability in terms of predicting 5HT7 inhibitory activity of the molecules, based on molecular property fields like steric, electrostatic, hydrophobic, hydrogen bond donor and hydrogen bond acceptor fields. This is evident from statistical parameters like conventional r2 and a cross validated (q2) values of 0.985, 0.743 for CoMFA and 0.970, 0.608 for CoMSIA, respectively. Predictive ability of the models to determine 5HT7 antagonistic activity is validated using a test set of 16 molecules that were not included in the training set. Predictive r2 obtained for the test set was 0.560 and 0.619 for CoMFA and CoMSIA, respectively. Steric, electrostatic fields majorly contributed toward activity which forms the basis for design of new molecules. Absorption, distribution, metabolism and elimination (ADME) calculation using QikProp 2.5 (Schrodinger 2010, Portland, OR) reveals that the molecules confer to Lipinski's rule of five in majority of the cases.